A tan-tpa covalent organic framework material, a preparation method thereof and application of visible light driven photocatalytic preparation of hydrogen peroxide

CN122978375APending Publication Date: 2026-10-27SHAOXING UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611409532.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]发明目的:针对现有COF光催化剂可见光吸收范围窄、现有D-A型结构分子内电荷转移作用偏弱、分子氧吸附活化能力不足,且缺少可协同解决三类问题的一体化骨架材料等不足,本发明第一目的提供一种强D-A型TAN-TPA共价有机框架光催化材料;第二目的提供该COF简便可控的溶剂热制备方法;第三目的提供该材料用于可见光催化制备过氧化氢的应用方案,依靠匹配度更高的给体-受体单元强化分子内电荷分离,借助扩展共轭骨架拓宽可见光吸收区间,依托丰富活性位点的微孔结构提升氧气吸附与活化效率,三者协同提升光催化产H2O2性能

Benefits of technology

[0017]有益效果:本发明构建能级高度匹配的TAN-TPAD-A 型共轭骨架,该材料依靠分子骨架结构设计同步解决可见光吸收、电荷分离、氧气吸附与活化三项关键问题,无需贵金属、金属离子掺杂或物理复合改性,合成路线仅一步溶剂热,原料易得、工艺温和,产物收率可达85%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978375A_ABST
    Figure CN122978375A_ABST
Patent Text Reader

Abstract

The application discloses a TAN-TPA covalent organic framework photocatalytic material, a preparation method thereof and application of the photocatalytic material in visible light driven photocatalytic preparation of hydrogen peroxide. A high-crystalline AA-stacked TAN-TPA COF is prepared by using an electron-deficient acceptor TAN-NH2 and an electron-rich donor TPA-CHO which are capable of matching energy levels as raw materials, uniformly tri-methyl benzene / 1,4-dioxane as a mixed solvent, glacial acetic acid as a catalyst and solvent thermal condensation at 120 DEG C. The material is designed by an integrated molecular structure, and simultaneously solves a plurality of short boards of the prior art: the visible light absorption range is widened by means of an extended conjugated narrow band gap skeleton; the intramolecular charge separation is enhanced by a strong coupling D-A unit, and the problem of weak charge interaction of a traditional D-A type COF is improved; and the oxygen adsorption and activation performance is improved by using rich active sites. Under visible light at normal temperature and pressure, the catalyst can stably drive water and oxygen to react to generate hydrogen peroxide, and the cumulative H2O2 production can reach 1000 mmol g⁻ 1 Above. The material is not doped with metal, is simple to synthesize and friendly to a catalytic environment, and is suitable for application in the field of photocatalytic preparation of hydrogen peroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of covalent organic framework porous organic materials and photocatalytic green synthesis technology, specifically involving an imine bond TAN-TPA covalent organic framework material, a solvothermal preparation process, and its application in the in-situ photocatalytic preparation of hydrogen peroxide in a visible light-driven pure water system. Background Technology

[0002] Hydrogen peroxide (H2O2) is a commonly used green oxidant in environmental remediation, fine chemicals, and medical and health fields. The industrial synthesis of anthraquinone is energy-intensive and generates organic wastewater. Photocatalysis utilizes solar energy, water, and molecular oxygen to produce H2O2 in situ. This process is mild and environmentally friendly, making it a promising alternative route. However, catalyst performance is a key factor limiting the practical application of this technology.

[0003] Covalent organic frameworks (COFs) are ordered cross-linked crystalline porous organic materials whose framework structure can be precisely controlled at the molecular level. They have been extensively studied in the photocatalytic production of H₂O₂. However, existing COF-based photocatalytic systems generally suffer from three problems that limit their catalytic activity:

[0004] 1. Limited visible light absorption range. Most COF frameworks have weak conjugation and wide band gaps, and can only absorb ultraviolet light or short-wavelength visible light, resulting in low utilization of long-wavelength visible light and insufficient solar energy utilization;

[0005] 2. Insufficient molecular oxygen adsorption and activation capacity. Conventional COFs have a limited number of pores and a low skeletal electron density, making it difficult to stably capture dissolved oxygen in the system. At the same time, they lack electron sites that can activate O2, making it difficult for oxygen molecules to be efficiently converted into H2O2 through the two-electron reduction pathway.

[0006] 3. High photogenerated electron-hole recombination efficiency. Some existing D-ACOFs suffer from insufficient donor-acceptor unit matching, weak intramolecular charge transfer, limited DA interaction, and rapid recombination of photogenerated carriers, resulting in a small number of effective electrons participating in the oxygen reduction reaction.

[0007] To address the aforementioned single problem, existing research has undertaken corresponding optimizations: broadening the conjugated structure to redshift light absorption, constructing porous structures to enhance oxygen adsorption, and introducing DA units to promote charge separation. As can be seen from existing public reports, most studies only address one or two of these problems. Integrated COF materials that simultaneously meet the three requirements of broadening the visible light response range, strengthening intramolecular DA charge separation, and enhancing molecular oxygen adsorption activation are still relatively rare. Summary of the Invention

[0008] Objectives of the Invention: To address the shortcomings of existing COF photocatalysts, such as narrow visible light absorption range, weak intramolecular charge transfer in existing DA-type structures, insufficient molecular oxygen adsorption and activation capabilities, and the lack of an integrated framework material that can synergistically solve these three problems, the first objective of this invention is to provide a strong DA-type TAN-TPA covalent organic framework photocatalytic material; the second objective is to provide a simple and controllable solvothermal preparation method for this COF; and the third objective is to provide an application scheme for the visible light photocatalytic production of hydrogen peroxide. This is achieved by relying on donor-acceptor units with higher matching degrees to enhance intramolecular charge separation, by expanding the visible light absorption range through an extended conjugated framework, and by relying on the microporous structure with abundant active sites to improve oxygen adsorption and activation efficiency. These three aspects synergistically enhance the photocatalytic H2O2 production performance.

[0009] Technical solution:

[0010] In a first aspect, the present invention provides a method for preparing a TAN-TPA covalent organic framework photocatalytic material, comprising the following steps:

[0011] (1) Feeding and Dispersion: Take a 10 mL Schlenk reaction tube and add 25.5 mg (0.03 mmol) of electron-deficient amino monomer TAN-NH2 and 10.0 mg (0.03 mmol) of electron-rich aldehyde monomer TPA-CHO. Figure 1 Add 1 ml of trimethylbenzene, 1 ml of 1,4-dioxane, and 0.1 ml of glacial acetic acid in sequence; sonicate the mixed suspension for 3 min to obtain a homogeneous dispersion.

[0012] (2) Solvothermal condensation reaction: The Schlenk reaction tube was sealed and placed in an oven at 120 °C for 72 h. The monomer underwent Schiff base imine condensation, forming a DA-type conjugated crystalline porous framework with molecular energy level matching and strong intramolecular charge transfer effect in situ.

[0013] (3) Washing, purification and drying: Cool naturally to room temperature, filter and collect solid; soak in fresh tetrahydrofuran for 24 h, changing the solvent every 6 h; then soak in acetone for 12 h, changing the solvent every 6 h; after washing, place the solid in a vacuum oven at 60 ℃ and dry for 4 h to obtain orange-red powder TAN-TPA COF, with a product yield of 85%.

[0014] Secondly, this invention provides a TAN-TPA covalent organic framework photocatalytic material prepared by the above method. This COF connects electron-deficient TAN units and electron-rich TPA units with matching energy levels via imine bonds, constructing a strongly interacting DA conjugated system. The crystal stacking mode is AA stacking (…). Figure 2 The extended conjugate framework modulates the material's optical bandgap to 1.92 eV, effectively broadening the visible light absorption range. Figure 4Nitrogen adsorption tests demonstrate that the material is rich in microporous structures, providing numerous sites for molecular oxygen adsorption and activation. Figure 3 );solid 13 The C1 NMR spectrum confirms the successful construction of the imine bond and the complete structure of the target DA-type conjugated framework. Figure 5 This material can simultaneously achieve a triple synergistic function of wide visible light capture, efficient photogenerated charge separation, and molecular oxygen enrichment and activation.

[0015] Thirdly, this invention provides the application of TAN-TPA COF in visible light-driven photocatalytic preparation of hydrogen peroxide, with specific testing procedures as follows:

[0016] Take 5 mg of TAN-TPA COF powder and disperse it in a mixture of 45 ml deionized water and 5 ml benzyl alcohol. Maintain a constant temperature of 20 ℃ using a circulating water bath. Before illumination, sonicate for 3 min to achieve uniform catalyst dispersion. In darkness, continuously purge with pure oxygen for 30 min to allow oxygen adsorption and enrichment through the micropores of the material, establishing adsorption equilibrium. Use a 300 W xenon lamp with a 420 nm UV cutoff filter as the visible light source, and continuously stir with magnetic stirring at 200 rpm throughout the reaction. Take 2 ml samples at preset time intervals and remove the solid catalyst using a 0.22 μm filter membrane. Mix 0.5 ml of the filtrate with an excess of 0.5 mM cerium sulfate solution and measure the absorbance at 318 nm. Calculate the cumulative yield by converting the H2O2 concentration in the system using a standard curve.

[0017] Beneficial effects: This invention constructs a TAN-TPAD-A type conjugated framework with highly matched energy levels. This material solves three key problems simultaneously by relying on molecular framework structure design: visible light absorption, charge separation, and oxygen adsorption and activation. It does not require noble metals, metal ion doping, or physical composite modification. The synthesis route is only one-step solvothermal, the raw materials are readily available, the process is mild, and the product yield can reach 85%. Attached Figure Description

[0018] Figure 1 Here is a schematic diagram of the chemical structure of the TAN-TPA synthesis route:

[0019] Figure 2 This is the Pawley refined powder X-ray diffraction pattern of TAN-TPA;

[0020] Figure 3 This is the nitrogen adsorption-desorption isotherm of TAN-TPA at 77K;

[0021] Figure 4 This is the solid-state UV-Vis diffuse reflectance spectrum of TAIN-TPA;

[0022] Figure 5This is the solid-state 13C nuclear magnetic resonance spectrum of TAN-TPA;

[0023] Figure 6 This is the curve showing the cumulative yield of H2O2 produced by TAN-TPA photocatalysis as a function of irradiation time.

[0024] in, Figure 1 This demonstrates the reaction pathway by which TAN-NH2 acceptor monomers and TPA-CHO donor monomers condense in a mixed solvent, catalyzed by glacial acetic acid, at 120°C to generate strong DA-type TAN-TPA.

[0025] Figure 2 The results of PXRD testing and Pawley refinement of the samples, with refinement parameter R. wp = 4.21%, R p = 2.88%, the experimental diffraction peaks match well with the AA stacked simulated spectrum, indicating that the material has a high degree of crystallinity;

[0026] Figure 3 Nitrogen adsorption isotherm display materials are mainly microporous, which can provide a large number of molecular oxygen adsorption sites;

[0027] Figure 4 Solid-state ultraviolet spectroscopy display materials can absorb a wide range of visible light. The optical band gap of 1.92 eV was obtained by Tauc fitting, which effectively improves the defect of narrow visible light absorption range of traditional COF.

[0028] Figure 5 The solid-state NMR characteristic carbon signal corresponds to the imine bond characteristic peak, confirming the stable connection of the donor and acceptor units and the successful construction of the strong DA conjugated framework;

[0029] Figure 6 The photocatalytic performance curves showed that the hydrogen peroxide yield continuously increased with prolonged illumination time, with a cumulative yield exceeding 1000 mmol g⁻ in 10 h. 1 This performance improvement stems from the synergistic effect of broad-spectrum light absorption, strong DA charge separation, and microporous oxygen activation. Detailed Implementation

[0030] Example 1: Preparation of TAN-TPA covalent organic framework material

[0031] Weigh TAN-NH2 (25.5 mg, 0.03 mmol) and TPA-CHO (10.0 mg, 0.03 mmol) into a 10 mL Schlenk reaction tube, add 1 mL of trimethylbenzene and 1 mL of 1,4-dioxane, and then add 0.1 mL of glacial acetic acid. Figure 1The mixture was sonicated for 3 min, the reaction tube was sealed, and placed in an oven at 120 °C for 72 h. After the reaction, it was allowed to cool naturally to room temperature, and the orange-red solid crude product was collected by filtration. Purification steps: Soaking in fresh tetrahydrofuran for 24 h, changing the solvent every 6 h; then soaking in acetone for 12 h, changing the solvent every 6 h; after washing, drying under vacuum at 60 °C for 4 h, finally obtaining 30 mg of orange-red TAN-TPA powder, yield 85%.

[0032] Product series characterization:

[0033] 1. PXRD Testing and Pawley Refinement: Experimental diffraction patterns show good matching with the stacked simulated structure. wp =4.21%, R p = 2.88%, high crystallinity of the material ( Figure 2 );

[0034] 2. 77 K Nitrogen Adsorption Test: The material is rich in microporous structure, which can effectively adsorb and enrich molecular oxygen at the active sites. Figure 3 );

[0035] 3. Solid-state UV-Vis diffuse reflectance spectrum: Tauc fitting band gap 1.92 eV, visible light response range broadened ( Figure 4 );

[0036] 4. Solid 13 C NMR: The presence of characteristic carbon signals of imine bonds confirms the successful synthesis of a strongly DA-type conjugated COF framework with energy level matching. Figure 5 ).

[0037] Example 2: Performance Test of TAN-TPA Photocatalytic Preparation of Hydrogen Peroxide

[0038] The photocatalytic reaction vessel had a volume of 100 ml. 5 mg of TAN-TPA prepared in Example 1 was weighed and dispersed in a mixture of 45 ml deionized water and 5 ml benzyl alcohol. A circulating water bath was used to maintain the temperature at 20 ℃. The catalyst was ultrasonically dispersed for 3 min in the dark to ensure uniform dispersion. Pure oxygen was continuously introduced into the dark environment for 30 min to allow for oxygen adsorption and enrichment through the micropores of the material. A 300 W xenon lamp was used as the light source, with a 420 nm cutoff filter to filter ultraviolet light. Continuous illumination with magnetic stirring at 200 rpm was maintained throughout the process. 2 ml samples were taken at fixed intervals, and solids were removed using a 0.22 μm filter membrane. 0.5 ml of the filtrate was mixed with an excess of 0.5 mM cerium sulfate solution, and the absorbance was measured at 318 nm to calculate the cumulative H2O2 yield.

[0039] Test results: With prolonged illumination time, the cumulative yield of hydrogen peroxide increased synchronously; after 10 hours of continuous illumination, the cumulative yield of H2O2 exceeded 1000 mmol g⁻1 ( Figure 6 This catalytic effect is achieved through the synergistic effect of three structural characteristics: the extended conjugated framework broadens visible light absorption, the strong DA molecular structure accelerates charge separation, and the microporous structure rich in active sites enhances oxygen adsorption and activation efficiency.

[0040] The above embodiments are merely preferred embodiments of the present utility model and are not intended to limit the scope of protection of the present utility model. Therefore, all equivalent changes made to the structure, shape, and principle of the present utility model should be covered within the scope of protection of the present utility model.

Claims

1. A method for preparing a TAN-TPA covalent organic framework photocatalytic material, characterized in that... Includes the following steps: (1) Feeding and dispersion: The amino monomer TAN-NH2 and the aldehyde monomer TPA-CHO were added to a Schlenk reaction tube, a mixed solvent of mesitylene and 1,4-dioxane was added, and glacial acetic acid was added as a condensation catalyst. The mixture was ultrasonically treated to obtain a uniform suspension. (2) Solvent thermal condensation reaction: The reaction tube was sealed and placed in an oven at 120°C for 72 h to produce a solid crude product by Schiff base condensation reaction. (3) Washing, purification and drying: After cooling to room temperature, the solid was collected and washed with tetrahydrofuran and acetone in sequence to remove unreacted monomers and oligomer impurities. After washing, it was vacuum dried to obtain orange-red powder TAN-TPA covalent organic framework material.

2. The preparation method of the TAN-TPA covalent organic framework photocatalytic material according to claim 1, characterized in that: In step (1), the amount of TAN-NH2 and TPA-CHO added was 0.03 mmol; the volume ratio of mesitylene to 1,4-dioxane was 1:1; the amount of glacial acetic acid added was 0.1 ml; and the ultrasonic time was 3 min.

3. The method for preparing the TAN-TPA covalent organic framework photocatalytic material according to claim 1, characterized in that: In step (3), tetrahydrofuran was soaked and washed for 24 h, and fresh tetrahydrofuran was replaced every 6 h; acetone was soaked and washed for 12 h, and fresh acetone was replaced every 6 h; vacuum drying temperature was 60 ℃, and drying time was 4 h.

4. A TAN-TPA covalent organic framework photocatalytic material prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The COF is formed by the condensation of TAN-NH2 and TPA-CHO via imine bonds, and has an AA stacked crystalline structure with an optical band gap of 1.92 eV. It is an orange-red powder with a microporous structure.

5. The application of the TAN-TPA covalent organic framework photocatalytic material according to claim 4 in the field of visible light-driven photocatalytic preparation of hydrogen peroxide.

6. The application according to claim 5, characterized in that... The photocatalytic preparation of hydrogen peroxide involves the following steps: dispersing the TAN-TPA catalyst in a mixed solution of deionized water and benzyl alcohol, ultrasonically dispersing it in the dark, and then purging it with pure oxygen in the dark; irradiating it with visible light using a 300 W xenon lamp equipped with a 420 nm cutoff filter, stirring the reaction at a constant temperature, and generating hydrogen peroxide in situ.

7. The application according to claim 6, characterized in that: The catalyst was fed at a rate of 5 mg, and the reaction system consisted of 45 mL of deionized water and 5 mL of benzyl alcohol. The reaction was carried out at a constant temperature of 20 °C. The mixture was purged with pure oxygen in the dark for 30 min, and the stirring speed was 200 rpm. The concentration of hydrogen peroxide was determined by cerium sulfate spectrophotometry.

8. The application according to claim 6, characterized in that: After 10 hours of continuous visible light irradiation, the cumulative production of hydrogen peroxide in the system can reach 1000 mmol g⁻ 1 above.